PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSETS (ROA) PADA PT BLUEBIRD TBK PERIODE 2013 – 2023 - Rahmawati, Mita; Sari, Widya Intan (Jurnal Nusa Manajemen, 2025)
This study aims to determine the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Bluebird Tbk for the period 2013- 2023. In this study using quantitative methods and the data used is secondary data in the form of financial statements of PT Bluebird Tbk 2013-2023. In this analysis method used is descriptive analysis, classical assumption test, coeffcient of determination, multiple regression analysis, and hypothesis testing, namely the t test with the f test which is analyzed using SPP Version 27. From the results of this study partially (t test) that the obtained tcount value of the Current Ratio (CR) variable is 0,787 > ttabel 2,306 at a level of error worth 5% significant value of 0,454 > 0,05 so it can be concluded from the results of this study that the Current ratio (CR) variable has no significant effect on Return on Assets. Partially (t test) produces a tcount of 2,730 > 2,306 at the 5% error rate, a significant value of 0,026 < 0,05 so it can be concluded from the results of this study that the Debt to Equity Ratio (DER) variable has a significant effect on Return on Assets (ROA). While the test results simultaneously (Test f) resulted in fcount < ftabel (3,731 < 4,26) and a significant value of 0,072 > 0,05 so it can be concluded that the results of the study Current Ratio (CR) and Debt to Equity Ratio (DER) have no significant effect on Return on Assets (ROA).